Daily Physical Activity, Functional Capacity and Quality of Life in Patients with COPD. (1st December 2014) - Dürr, Selina; Zogg, Stefanie; Miedinger, David; Steveling, Esther Helen; Maier, Sabrina; Leuppi, Jörg Daniel
Abstract Introduction: In the therapy of chronic obstructive pulmonary disease (COPD), it is a major goal to improve health-related quality of life (HRQOL). Patients with COPD often suffer from exertional dyspnea and adopt a sedentary lifestyle, which could be associated with poorer HRQOL. The aim of this study was to investigate the independent association of objectively measured daily physical activity and functional capacity with HRQOL in patients with COPD. Methods: In this cross-sectional study conducted at the University Hospital Basel, Switzerland, 87 stable patients (58.6% male, mean age: 67.3 ± 9.6 yrs) with COPD in GOLD grades I (n = 23), II (n = 46), III (n = 12) and IV (n = 6) were investigated. To assess HRQOL, the COPD assessment test (CAT) was completed. Patients performed spirometry and 6-min walk test. Physical activity was measured by the SenseWear Mini Armband on 7 consecutive days. By performing a multiple linear regression analysis, independent predictors of CAT score were identified. Results: Age (β = −0.39, p = 0.001), average daily steps (β = −0.31, p = 0.033) and 6-min walk distance (β = −0.32, p = 0.019) were found to be independent predictors of CAT score, whereas physical activity duration above 3 METs (p = 0.498) and forced expiratory volume in 1 s in% of predicted (p = 0.364) showed no significant association. Conclusions: This study showed that average daily steps and functional capacity are independent determinants of HRQOL in patients with COPD. This emphasizes the importance to remain active and mobile, which is associated with better HRQOL.